Dynamics in Central Europe: A labor flow approach - Vladislav Flek; Martina Mysíková (Charles University in Prague, Institute of Economic Studies (IES), 2012)
We analyze labor market flows and unemployment in the Czech Republic (CR), Slovakia and Poland over the period 2004-2007. Relative involvement of working-age population in gross labor market flows is approximately five times lower in central Europe than in the U.S. /UK. Yet, compared to neighboring countries, the CR suffers more from unemployment rigidity, as evidenced most convincingly by a relatively weakernet flowof workers from unemployment to employment. This net flow alone would cut the unemployment rate in Poland more than twice as fast as in the CR. The CR lags behind in creating jobs forthe unemployed, particularly for men, individuals with primary education, and for the 55-65 age group.
Keywords: E24; J60; J63; J64; 330; EU-SILC; labor market flows; longitudinal data; unemployment